MotherRock LP : natural gas calendar spread - Varma, Jayanth (London : SAGE Publications Ltd, 2017)
The case deals with risk management issues related to a large calendar spread position in a highly seasonal and volatile commodity (natural gas). Apart from fundamental factors affecting the supply and demand for natural gas, the spread is also exposed to transient price movements in the futures market itself. The case is designed to be used in courses on derivatives, alternative investments and hedge funds.
Originally published: Varma, J. (2013). MotherRock LP Natural gas calendar spread. F&A05010. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; MotherRock LP; Natural gas -- Purchasing -- Case studies; Gas industry -- Privatization -- Case studies; Gas industry -- Risk management -- Case studies